Does Walking Speed Mediate the Association Between Visual Impairment and Self‐Report of Mobility Disability? The Salisbury Eye Evaluation Study. Issue 8 (15th July 2014) - Swenor, Bonnielin K.; Bandeen‐Roche, Karen; Muñoz, Beatriz; West, Sheila K.
<x xml:space="preserve">Abstract</x> Objectives To determine whether performance speeds mediate the association between visual impairment and self‐reported mobility disability over an 8‐year period. Design Longitudinal analysis. Setting Salisbury, Maryland. Participants Salisbury Eye Evaluation Study participants aged 65 and older (N = 2, 520). Measurements Visual impairment was defined as best‐corrected visual acuity worse than 20/40 in the better‐seeing eye or visual field less than 20°. Self‐reported mobility disability on three tasks was assessed: walking up stairs, walking down stairs, and walking 150 feet. Performance speed on three similar tasks was measured: walking up steps (steps/s), walking down steps (steps/s), and walking 4 m (m/s). Results For each year of observation, the odds of reporting mobility disability was significantly greater for participants who were visually impaired (VI) than for those who were not (NVI) (odds ratio (OR) difficulty walking up steps = 1.58, 95% confidence interval (CI) = 1.32–1.89; OR difficulty walking down steps = 1.90, 95% CI = 1.59–2.28; OR difficulty walking 150 feet = 2.11, 95% CI = 1.77–2.51). Once performance speed on a similar mobility task was included in the models, VI participants were no longer more likely to report mobility disability than those who were NVI (OR difficulty walking up steps = 0.84, 95% CI = 0.65–1.11; OR difficulty walking down steps = 0.96, 95% CI = 0.74–1.24; OR difficulty walking 150 feet = 1.22, 95% CI = 0.98–1.50). Conclusion Slower performance speed in VI individuals largely accounted for the difference in the odds of reporting mobility disability, suggesting that VI older adults walk slower and are therefore more likely to report mobility disability than those who are NVI. Improving mobility performance in older adults with visual impairment may minimize the perception of mobility disability.